Best Treatment Option for Patients With Refractory Aggressive B-Cell Lymphoma in the CAR-T Cell Era: Real-World Evidence From GELTAMO/GETH Spanish Groups - Bastos-Oreiro, Mariana; Gutierrez, Antonio; Reguera, Juan Luís; Iacoboni, Gloria; López-Corral, Lucía; Terol, María José; Ortíz-Maldonado, Valentín; Sanz, Jaime; Guerra-Dominguez, Luisa; Bailen, Rebeca; Mussetti, Alberto; Abrisqueta, Pau; et al. (Frontiers in Immunology, 2022)
Real-world evidence comparing the efficacy of chimeric antigen receptor (CAR) T-cell therapy against that of the previous standard of care (SOC) for refractory large B-cell lymphoma (LBCL) is scarce. We retrospectively collected data from patients with LBCL according to SCHOLAR-1 criteria treated with commercial CAR T-cell therapy in Spain (204 patients included and 192 treated, 101 with axicabtagene ciloleucel [axi-cel] and 91 with tisagenlecleucel [tisa-cel]), and compared the results with a historical refractory population of patients (n = 81) obtained from the GELTAMO-IPI study. We observed superior efficacy for CAR-T therapy (for both axi-cel and tisa-cel) over pSOC, with longer progression-free survival (PFS) (median of 5.6 vs. 4.6 months, p=<0.001) and overall survival (OS) (median of 15 vs. 8 months, p<0.001), independently of other prognostic factors (HR: 0.59 (95%CI: 0.44-0.80); p<0.001] for PFS, and 0.45 [(95%CI: 0.31-0.64)] for OS). Within the CAR-T cohort, axi-cel showed longer PFS (median of 7.3 versus 2.8 months, respectively, p=0.027), and OS (58% versus 42% at 12 months, respectively, p=0.048) than tisa-cel. These differences were maintained in the multivariable analysis. On the other hand, axi-cel was independently associated with a higher risk of severe cytokine release syndrome and neurotoxicity. Our results suggest that the efficacy of CAR-T cell therapy is superior to pSOC in the real-world setting. Furthermore, axi-cel could be superior in efficacy to tisa-cel, although more toxic, in this group of refractory patients according to SCHOLAR-1 criteria.